2021
DOI: 10.1016/j.pnpbp.2021.110260
|View full text |Cite
|
Sign up to set email alerts
|

Philosophy for children and mindfulness during COVID-19: Results from a randomized cluster trial and impact on mental health in elementary school students

Abstract: Background: Preliminary evidence suggests that the COVID-19 pandemic has had a negative impact on children's mental health. Given these problems can have significant impacts throughout the lifespan, preventing the negative repercussions of COVID-19 on children's mental health is essential. Philosophy for children (P4C) and mindfulness-based interventions (MBIs) show promise in this regard. Objective: The goal of the present study was to compare the impact of online MBI and P4C interventions on mental health, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 34 publications
0
74
0
10
Order By: Relevance
“…The studies identified by this review were carried out in different countries across Asia [26, 27•, 28, 29•, 30, 31], the Americas (four, with two interventions from the USA [32,33] and two from Canada [34,35], Europe [36•], Africa [37] and Oceania [38]).…”
Section: When and Where Were The Interventions Implemented?mentioning
confidence: 99%
See 4 more Smart Citations
“…The studies identified by this review were carried out in different countries across Asia [26, 27•, 28, 29•, 30, 31], the Americas (four, with two interventions from the USA [32,33] and two from Canada [34,35], Europe [36•], Africa [37] and Oceania [38]).…”
Section: When and Where Were The Interventions Implemented?mentioning
confidence: 99%
“…The interventions were carried out between 2006 and 2020, although four studies did not report when the post-disaster intervention occurred (and how long after the disaster) or its duration. Four interventions were implemented while the COVID-19 pandemic was happening [30,32,34,35], two interventions were carried out within a few months of a disaster [29•, 37] and three interventions were implemented 1 year after the disaster or shortly after the first anniversary [26,33,38]. Interventions for child mental health were performed in response to pandemics-mostly COVID-19 [29•, 30, 32, 34, 35, 37], earthquakes [31, 36•, 38], floods [27•], hurricanes [33], tsunamis [31], typhoons [26] and volcanic eruptions [28].…”
Section: When and Where Were The Interventions Implemented?mentioning
confidence: 99%
See 3 more Smart Citations